Familial amyloid polyneuropathy in Portugal: New genes modulating age‐at‐onset. Issue 2 (20th December 2016) - Santos, Diana; Coelho, Teresa; Alves‐Ferreira, Miguel; Sequeiros, Jorge; Mendonça, Denisa; Alonso, Isabel; Lemos, Carolina; Sousa, Alda
Abstract: Objectives: Familial amyloid polyneuropathy (FAP ATTRV30M) shows a wide variation in age‐at‐onset (AO) between clusters, families, and among generations. We will now explore some candidate genes involved in altered disease pathways in order to assess their role as genetic modifiers of AO, using a family‐centered approach. Methods: We analyzed 62 tagging SNPs from nine genes‐ NGAL, MMP‐9, BGN, MEK1, MEK2, ERK1, ERK2, HSP27, and YWHAZ – in a sample of 318 V30M Portuguese patients (106 families), currently under follow‐up. A generalized estimating equation analysis was used to take into account nonindependency of AO between relatives. Also, an in silico analysis was performed in order to assess the functional impact of significant variants associated with AO. Results: We found for the first time variants from six genes ( NGAL, BGN (in the female group), MEK1, MEK2, HSP27, and YWHAZ ) that were significantly associated with early‐ and/or late‐onset. Then, we confirmed a strong synergistic interaction between NGAL and MMP‐9 genes. Additionally, by an in silico analysis, we found some variants for MEK1 gene that may alter binding of the transcription factors and that influence the regulation of gene expression regarding microRNA binding sites and splicing regulatory factors. Interpretation: These findings showed that different genetic factors can modulate differently the onset of disease's symptoms and revealed new mechanisms with clinical implications in the genetic counseling and follow‐up of mutation carriers and could contribute for development of potential therapeutical targets.